Review of Cermatobius Haase, 1885 (Chilopoda: Henicopidae) of China and Neotype Designation for Cermatobius longicornis (Takakuwa, 1939) - Ma, Hui-Qin; Song, Da-Xiang; Zhu, Ming-Sheng (Zootaxa, 2007)
A review of Chinese occurences of the genus Cermatobius Haase, 1885 (Lithobiomorpha: Henicopidae) is based on both male and female specimens. Diagnoses, descriptions, distributions, and figures are presented for the two Chinese species, C. longicornis (Takakuwa, 1939) and C. longitarsis (Verhoeff, 1934a); at the same time, we designated a neotype for C. longicornis.